TRENDS OF DIAGNOSTIC ASSESSMENT IN EDUCATIONAL EVALUATION AND ASSESSMENT JOURNALS IN INDONESIA - Lumaur Ridlo; Abdullah Ridlo; Lulu Alfiyah; Robit Totussangadah (MUMTAZ : Jurnal Pendidikan Agama Islam, 2024)
Diagnostic assessment is important in evaluating learning to identify students' readiness, learning difficulties, and conceptual errors to maintain the quality of education. This study aims to analyze research trends on the theme of diagnostic assessment in Indonesian journals on educational evaluation and assessment during the period 2014 to 2025. This research employs a systematic review of articles published in educational evaluation and assessment journals indexed in SINTA. The results of this systematic review indicate that the primary focus of research in this field is the development and validation of diagnostic instruments, with a predominance of quantitative approaches and research and development methods. Research subjects primarily involve high school students, while studies involving elementary school students or educators remain limited. The use of qualitative and mixed methods is still rare. These findings indicate that there is still room for expanding the approaches and focus of diagnostic assessment research in Indonesia to generate a more comprehensive understanding that can support educational practices that are more responsive to students' needs. This study can serve as an initial reference for the development of future research and practices in diagnostic assessment.